Understanding the role of post-CCVD synthetic impurities, functional groups and functionalization-based oxidation debris on the behaviour of carbon nanotubes as a catalyst support in cyclohexene hydrogenation over Pd nanoparticles. Issue 91 (16th September 2016) - Puskas, R.; Sápi, A.; Kukovecz, Á.; Kónya, Z.
Abstract : Tuning of the surface modification has a striking effect on the physical and chemical properties of CNTs in surface chemical processes. Abstract : A new method has been developed to separately study the effects of (i) impurities resulting from the catalytic chemical vapor deposition synthesis, (ii) the attached functional groups and (iii) the oxidation debris on the properties of carboxyl-functionalized multiwall carbon nanotubes (CNTs) by incorporating a Soxhlet-extractor enhanced acetone washing process into the synthesis method. Pd nanoparticles supported on the carbon nanotubes were investigated in the hydrogenation of cyclohexene to cyclohexane. Despite the fact that the specific surface area and the Pd dispersion were both low, the Pd/CNT catalyst with post-synthetic impurities showed ∼20 times higher catalytic activity compared to functional group free, acetone-washed samples. Meanwhile oxidation debris originating from the functionalization was found to affect both the specific surface area and the G/D ratio obtained from Raman spectra, it had slight effect on the size of the supported Pd nanoparticles or the catalytic activity. On the other hand, functional groups have a significant effect on the catalytic activity without influencing the specific surface area, the G/D ratio or the Pd nanoparticle dispersion.